Inclusion in Finland: Myths and Realities - Jahnukainen Markku; Hienonen Ninja; Lintuvuori Meri; Lempinen Sonia (Springer, 2025)
Although inclusive education is a strong trend in education policy around the globe, there are different definitions and variations used in different nations. The case of Finland is interesting, because the long-term direction of the Finnish school system has supported every child’s right to participate in education, but inclusive education is not mentioned or defined anywhere in education legislation. This absence of definition not only leaves the defining to the parties concerned, but also adds to creating inclusive myths and varying realities in everyday life. Meanwhile, in public discussion, there has been a constant and quite polarised debate about putting students with support needs in regular classrooms. The recent Government Program (2019) in Finland states that special education legislation should be investigated from the point of view of students as well as teachers’ wellbeing. In order to define the current state and equality of the Finnish support system, the Ministry of Education and Culture has established a working group as part of the “Right to Learn” initiative 2020–2022. In this chapter, we discuss the historical development of Finnish inclusion and contrast myths and realities of the Finnish model in supporting students with support needs in the light of international trends in inclusive and special education. We also discuss possible future trends of inclusive education in the Finnish context.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling